Dialek Betawi Jakarta - Siti Jubaidah (Tsaqofah, 2020)
The native Jakartans call themselves the Betawi people or the Betawi Malay or the Selam people (only after independence was achieved, their names were better known as the people of Jakarta). The language he uses is called Malay or Betawi Malay (also only after independence, his name is better known as the Jakarta language). As for the language spoken on the edge of Jakarta, in areas bordering Sundanese, he calls it the name Betawi Ora '. The Betawi language or Betawi dialect has regional variations, in other words, the Betawi dialect experiences differences between one region and another in Jakarta.